Co-hydrothermal liquefaction of phumdi and paragrass an aquatic biomass: Characterization of bio-oil, aqueous fraction and solid residue. (June 2022) - Biswas, Bijoy; Sahoo, Dinabandhu; Sukumaran, Rajeev K.; Krishna, Bhavya B.; Kumar, Jitendra; Reddy, Yenumala Sudhakara; Adarsh, Velayudhanpillai Prasannakumari; Puthiyamadam, Anoop; Mallapureddy, Kiran Kumar; Ummalyma, Sabeela Beevi; Bhaskar, Thallada
Abstract: Hydrothermal liquefaction (HTL) of wet aquatic biomasses namely, Paragrass (PG) and Phumdi (PH) and a mixture of PG-PH were examined. Different reaction parameters such as temperature (260–300 °C) and solvents (water, ethanol, and methanol) were screened to optimize the products distribution. Maximum bio-oil yield (13.82 wt%) was observed for PG under water solvent. In case of mixture of biomass (PG-PH), maximum bio-oil yield (11.66 wt%) was observed with ethanol solvent. In case of PH biomass, maximum conversion of 98.4 wt% was found with water solvent at 300 °C. Individual liquefaction of PH and PG biomass majorly produced ester compounds (49.21 and 52.58%, respectively) in the presence of ethanol as solvent. Co-liquefaction bio-oil consisted of phenolic compounds (67.49%) with ethanol as solvent followed by 50.84% in water and 49.59% in methanol. In water solvent, PH biomass showed higher carbon conversion efficiency (69.8%). The PG-PH hydrothermal liquefaction derived aqueous fraction showed significantly higher (57000 mg/L) organic carbon. Obvious difference in the product yields and compounds formed during liquefaction reaction is ascribed to the distinct effect of solvents and temperatures on biomass macromolecular breakdown. Highlights: Hydrothermal liquefaction of Loktak Lake aquatic biomass was studied. Maximum bio-oil (13.82 wt%) was obtained with Para grass under water solvent. Higher % of nitrogen and ester compounds was obtained for individual biomass HTL. PG-PH mixture HTL bio-oil majorly contained of phenolic compounds (67.49%).